(untitled) (BIRDEM Medical Journal, 2020)
Background: Patients of stroke or transient ischaemic attacks (TIA) are at risk of further stroke. Our objective was to study patients admitted with stroke/TIA regarding their knowledge about risk factors for having anew event of stroke/TIA, possible associations between patient characteristics and patients’ knowledge about risk factors, and patients’ knowledge about their preventive treatment for stroke/TIA. Methods: A questionnaire was used for 200 patients with stroke/TIA diagnoses. We asked 13 questions about diseases/conditions and lifestyle factors known to be risk factors and four questions regarding other diseases/ conditions (“distractors”). Additional questions concerned with the patients’ social and functional status and their drug use were asked. Categorical variables were analyzed using chi square test, while one-way analysis of variance and univariate analysis of variance were used for continuous variables. Logistic regression was employed to describe risk. A p value of, p < 0.05 was considered statistically significant. Results: The risk factors that were most often identified by the patients were Diabetes(75.9%), hypertension(83.3%), previous stroke or TIA(81.5%), smoking (85.2%), regular exercise(75.9%), older age(83.3%), overweight (75.9%) and patients with ischemic heart disease (70.4%). Atrial fibrillation and carotid stenosis were identified by less than 50% of the patients. 44.5% of the patients could identify 10 or more stroke/TIA risk factors. We observed that higher age, having a diagnosis of cerebral infarction/TIA, patients residing in urban area, high income group, businessman/retired service holder, family history of cardiovascular disease, past history of stroke / TIA were related to better knowledge of stroke/TIA risk factors. Anticoagulants and antiplatelets are important drugs for stroke/TIA prevention but only 20(9.3%) of the patients who reported anticoagulants and 76(35.2%) of the patients taking these drugs marked them as intended for prevention. Conclusion: Knowledge about diabetes, hypertension and smoking as risk factors was good, and patients who suffered from atrial fibrillation or carotid stenosis seemed to be less informed about these conditions as risk factors. The knowledge level was low regarding the use of anticoagulants and antiplatelets for stroke/TIA prevention. Better patient educational strategies for stroke/TIA patients should be developed. Furthermore, individuals with less knowledge should be given special consideration when developing strategies and programmes thus improving awareness of stroke risk factors. Birdem Med J 2021; 11(1): 22-29